A Long-Term Cultivation of an Anaerobic Methane-Oxidizing Microbial Community from Deep-Sea Methane-Seep Sediment Using a Continuous-Flow Bioreactor - Aoki, Masataka (Public Library of Science, 2014)
Anaerobic oxidation of methane (AOM) in marine sediments is an important global methane sink, but the physiological characteristics of AOM-associated microorganisms remain poorly understood. Here we report the cultivation of an AOM microbial community from deep-sea methane-seep sediment using a continuous-flow bioreactor with polyurethane sponges, called the down-flow hanging sponge (DHS) bioreactor. We anaerobically incubated deep-sea methane-seep sediment collected from the Nankai Trough, Japan, for 2,013 days in the bioreactor at 10°C. Following incubation, an active AOM activity was confirmed by a tracer experiment using (13)C-labeled methane. Phylogenetic analyses demonstrated that phylogenetically diverse Archaea and Bacteria grew in the bioreactor. After 2,013 days of incubation, the predominant archaeal components were anaerobic methanotroph (ANME)-2a, Deep-Sea Archaeal Group, and Marine Benthic Group-D, and Gammaproteobacteria was the dominant bacterial lineage. Fluorescence in situ hybridization analysis showed that ANME-1 and -2a, and most ANME-2c cells occurred without close physical interaction with potential bacterial partners. Our data demonstrate that the DHS bioreactor system is a useful system for cultivating fastidious methane-seep-associated sedimentary microorganisms.